A 1:2 co-crystal of 2,2′-thiodibenzoic acid and triphenylphosphane oxide: crystal structure, Hirshfeld surface analysis and computational study - Tan, Sang Loon *; Tiekink, Edward R. T. * (International Union of Crystallography, 2018)
The asymmetric unit of the title co-crystal, 2,20-thiodibenzoic acid–triphenylphosphane oxide (1/2), C14H10O4S2C18H15OP, comprises two molecules of 2,20 -thiodibenzoic acid [TDBA; systematic name: 2-[(2-carboxyphenyl)sulfanyl]benzoic acid] and four molecules of triphenylphosphane oxide [TPPO;systematic name: (diphenylphosphoryl)benzene]. The two TDBA molecules are twisted about their disulfide bonds and exhibit dihedral angles of 74.40 (5) and 72.58 (5) between the planes through the two SC6H4 residues. The carboxylic acid groups are tilted out of the planes of the rings to which they are attached forming a range of CO2/C6 dihedral angles of 19.87 (6)–60.43 (8). Minor conformational changes are exhibited in the TPPO molecules with the range of dihedral angles between phenyl rings being 2.1 (1) to 62.8 (1). In the molecular packing, each TDBA acid molecule bridges two TPPO molecules via hydroxy-O—HO(oxide) hydrogen bonds to form two three-molecule aggregates. These are connected into a three-dimensional architecture by TPPO-C—HO(oxide, carbonyl) and TDBA-C—H(oxide, carbonyl) interactions. The importance of HH, OH/HO and CH/HC contacts to the calculated Hirshfeld surfaces has been demonstrated. In terms of individual molecules, OH/HO contacts are more important for the TDBA (ca 28%) than for the TPPO molecules (ca 13%), as expected from the chemical composition of these species. Computational chemistry indicates the four independent hydroxy-O—HO(oxide) hydrogen bonds in the crystal impart about the same energy (ca 52 kJ mol-1), with DTBA-phenyl-C—HO(oxide) interactions being next most stabilizing (ca 40 kJ mol-1).